Testing Differential Holistic Processing Within a Face: No Evidence of Asymmetry from the Complete Composite Task - Shyi, Gary C.-W.; Wang, Chao-Chih (Frontiers in Psychology, 2016)
The composite face task is one of the most popular research paradigms for measuring holistic processing of upright faces. The exact mechanism underlying holistic processing remains elusive and controversial, and some studies have suggested that holistic processing may not be evenly distributed, in that the top-half of a face might induce stronger holistic processing than its bottom-half counterpart. In two experiments, we further examined the possibility of asymmetric holistic processing. Prior to Experiment 1, we confirmed that perceptual discriminability was equated between top and bottom face halves; we found no differences in performance between top and bottom face halves when they were presented individually. Then, in Experiment 1, using the composite face task with the complete design to reduce response bias, we failed to obtain evidence that would support the notion of asymmetric holistic processing between top and bottom face halves. To further reduce performance variability and to remove lingering holistic effects observed in the misaligned condition in Experiment 1, we doubled the number of trials and increased misalignment between top and bottom face halves to make misalignment more salient in Experiment 2. Even with these additional manipulations, we were unable to find evidence indicative of asymmetric holistic processing. Taken together, these findings suggest that holistic processing is distributed homogenously within an upright face.